Molecular Diagnosis of Allergy: The Pediatric Perspective - Dramburg, Stephanie; Matricardi, Paolo Maria (Frontiers in Pediatrics, 2019)
In times of “Precision Medicine” it is fundamental to identify the individual disease phenotype in order to provide an individualized therapy for every patient. This concept is also becoming increasingly important for the treatment of allergic diseases. Thanks to the biological engineering of recombinant and native allergens for the assessment of allergen-specific IgE antibodies, it is now possible to easily obtain the individual sensitization profile of a patient. This allows the allergist to precisely identify the primary elicitor of an IgE response and, based on this knowledge, to choose the best treatment option. Several studies have observed the longitudinal evolution of sensitization profiles and identified a phenomenon termed “molecular spreading”, which describes a broadening of the recognized allergen spectrum from a source over time. Additionally, the identification of marker proteins, which can trigger an IgE response or correlate with an increased risk for certain clinical symptoms, helps to establish an individual risk profile. This information may not only affect the decision-making concerning immunotherapy, but also opens up avenues for future investigations with regard to prevention strategies. We provide here an overview on the role of individual sensitization patterns and their predictive value.